2015
DOI: 10.2147/ijn.s73096
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-controllable electrospun fibers promote tubular structure formation by endothelial progenitor cells

Abstract: Controlling the thickness of an electrospun nanofibrous scaffold by altering its pore size has been shown to regulate cell behaviors such as cell infiltration into a three-dimensional (3D) scaffold. This is of great importance when manufacturing tissue-engineering scaffolds using an electrospinning process. In this study, we report the development of a novel process whereby additional aluminum foil layers were applied to the accumulated electrospun fibers of an existing aluminum foil collector, effectively red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, the microvascular epithelial cells showed sparse extracellular matrix on the L-PLA scaffolds with pore size from 38 to 150 lm, while multilayered lining was formed on the scaffolds with pore size \38 lm (Zeltinger et al 2001). It was also shown that the depth of invasion (160 lm after 4 h) of endothelial progenitor cells into electrospun fibrous scaffold and their further colonization was increased with increasing pore size ([45 lm) (Hong et al 2015). Another study showed only 100 lm infiltration of the endothelial progenitors into electrospun fibrous scaffolds with pore size \20 lm after 7 days of culturing (Blakeney et al 2011).…”
Section: Pore Sizes For the Regeneration Of Other Connective Tissuesmentioning
confidence: 98%
“…However, the microvascular epithelial cells showed sparse extracellular matrix on the L-PLA scaffolds with pore size from 38 to 150 lm, while multilayered lining was formed on the scaffolds with pore size \38 lm (Zeltinger et al 2001). It was also shown that the depth of invasion (160 lm after 4 h) of endothelial progenitor cells into electrospun fibrous scaffold and their further colonization was increased with increasing pore size ([45 lm) (Hong et al 2015). Another study showed only 100 lm infiltration of the endothelial progenitors into electrospun fibrous scaffolds with pore size \20 lm after 7 days of culturing (Blakeney et al 2011).…”
Section: Pore Sizes For the Regeneration Of Other Connective Tissuesmentioning
confidence: 98%
“…Cellular tubulogenesis assay is a common tool to mimic many stages of in vivo angiogenesis, including cell migration, proliferation, vessel branching, and anastomosis processes. 49 , 50 For this assay, HUVECs are supported on Matrigel, and the effects of biomaterials or molecules are examined on the tubular networking of cells. The nanosized bioactive glasses that could release silicate ions at 2.87–8.39 µg/mL presented significantly higher number of tubules and more stable tubular structure when compared to the glass-free control group.…”
Section: Effects Of Si Ion Release On Angiogenic Events (In Vitro Andmentioning
confidence: 99%
“…Figure b,c presents a cross-sectional view of 3D aligned scaffolds with 146 μm thickness, demonstrating the high porosity and excellent alignment of nanofibers. As the nanofiber porosity greatly affects the cell seeding into the inner space of 3D scaffolds, the ES time effect was investigated to control the nanofiber scaffold porosity . Three types of single-layer nanofiber scaffolds were produced (Figure d–f).…”
Section: Results and Discussionmentioning
confidence: 99%